2018
DOI: 10.2478/jvetres-2018-0060
|View full text |Cite
|
Sign up to set email alerts
|

Results of a 16-week safety assurance study with rats fed genetically modified Bt maize: effect on growth and health parameters

Abstract: IntroductionThe influence of feeding genetically modified MON 810 hybrid maize on the growth and haematological and biochemical indices of rats was tested.Material and MethodsTwo conventional (non-GM) and two test (MON 810) lines of maize were used in semi-purified diets at the level of 40% w/w. The non-GM I, MON 810 I, non-GM II, and MON 810 II maize lines were near-isogenic. A total of 40 male 6-week-old Wistar-derived rats were assigned to four equal feeding groups corresponding to the four maize lines for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Systematic evaluation of potential side effects of Bt-maize versus conventional maize have been carried out to assess any significant differences using animal feeding studies. These studies concluded that the Bt-maize was as safe and nutritious as existing conventional corn varieties 4,13,14 . However, these results were questioned by the Séralini lab 15 who after reanalysis of Monsanto’s data announced that the results of the three GMO studies were sex- and often dose-dependent and showed side effects associated with the kidney and liver, although these were not consistent between the three studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic evaluation of potential side effects of Bt-maize versus conventional maize have been carried out to assess any significant differences using animal feeding studies. These studies concluded that the Bt-maize was as safe and nutritious as existing conventional corn varieties 4,13,14 . However, these results were questioned by the Séralini lab 15 who after reanalysis of Monsanto’s data announced that the results of the three GMO studies were sex- and often dose-dependent and showed side effects associated with the kidney and liver, although these were not consistent between the three studies.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last years, numerous research activities have focused on the safety assessment of such genetically modified crops, using various animal models, including mouse 3 , rat 47 , cattle 8 , salmon 9 , poultry 7,10 and pig 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Scholtz et al (2010) found no deterioration of the immune system in quail when fed on genetically modified maize. The experiment Szymczyk et al (2018) Indicators metabolism in rats fed a diet with conventional or genetically modified (MON 810) maize for 16 weeks was similar. The authors also no found significant differences in the body weight and the relative weight of the organs of rats, some histopathological changes in the liver, kidney and spleen were not related to nutrition.…”
Section: Introductionmentioning
confidence: 91%
“…The pre-testing for the safety of GM crops in several areas has indicated no evidence of any adverse reactions ( Kamle et al., 2017 ). Although the negative health consequences of GM crops consumption are reported on rats, analyses of most of the studies about the safety of GM crops, indicated no human health consequences ( Szymczyk et al., 2018 ; Giraldo et al., 2019 ).…”
Section: Perspectives On the Criticisms Of Gm Crops Incorporation Int...mentioning
confidence: 99%